A modeling method for complex system using hybrid method. (2nd January 2017) - Xu, Xiaoping; Wang, Feng
Abstract: The branch of complex system spans over a wide range of areas from physical and technological systems to social and biological systems. As the first step of any complex system analysis, modeling is an important task in scientific studies field. Then both the theory and practice of complex system modeling has been considered in recent years. It is well known that system identification is the theory and methods of establishing mathematical models of complex systems. Consequently, an identification approach for a class of complex nonlinear system is put forward in this paper. The idea of the identification method employs a system model composed with classical models so as to transform the system structure identification problem into a combinatorial optimization problem initially. Then, the artificial fish swarm optimization algorithm is used to synchronously implement the identification on the system's structure and parameters. Finally, in simulation, compared with other algorithm, simulation results show that the proposed scheme is feasible.